PENGUJIAN SAH TIDAKNYA PENETAPAN TERSANGKA DALAM KERANGKA PRAPERADILAN - Alfiananda, Rizky Fakhry (Wacana Hukum, 2018)
AbstractA pretrial construction as it has been regulated in the Indonesian CriminalProcedure Code had instantly changed after the Constitutional Court decision Number : 21/PUU-XII/2014 that being announced on April 28, 2015. The pretrial construction was initially authorized only to examine and decide the validity of arrest and detention, the validity of investigation and prosecution termination, and the demand for compensation or rehabilitation. The authority of the pretrial by a quo decision was then expanded by adding an examination on the validity of inquiry, the validity of confiscation, and the validity of suspect determination. Although a quo decision is reputed tohave exceeded the authority of the Constitutional Court because it is judged of creating a new norm, a quo decision remains final and tied so that it should be considered as a complement to the Indonesian Criminal Procedure Code.AbstrakKonstruksi praperadilan sebagaimana diatur di dalam BAB X Bagian Kesatu KUHAP seketika berubah pasca dibacakannya putusan Mahkamah Konstitusi Nomor : 21/PUU-XII/2014 pada tanggal 28 April 2015. Praperadilan yang konstruksi awalnya hanya berwenang memeriksa dan memutus sah atau tidaknya suatu penangkapan dan penahanan, sah atau tidaknya penghentian penyidikan dan penghentian penuntutan, serta permintaan ganti kerugian atau rehabilitasi, oleh putusan a quo kewenangannya diperluas dengan menambahkan pengujian mengenai sah tidaknya penggeledahan, sah tidaknya penyitaan, serta sah tidaknya penetapan tersangka. Meskipun putusan a quo dinilai melebihi kewenangan Mahkamah Konstitusi karena dinilai telah membuat norma baru, namun putusan a quo tetap bersifat final dan mengikat sehingga harus dianggap sebagai hukum pelengkap KUHAP.